ANALYSIS OF VILLAGE ADMINISTRATIVE INFORMATION SYSTEM MODELS TO IMPROVE GOOD PUBLIC GOVERNANCE - Andi Kusuma; Siti Amerieska; Fadelis Sukya; Indra Lukmana Putra; Bagas Brian Pratama (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
This study aims to analyze and design the modeling of the village administration information system. This design aims to improve the quality of village governance because the village government is the foremost representative in the state order that is very close to people's lives. The research method uses Research and Development, while the analysis model uses the Business Process Management System (BPMS) framework. The research stage starts with problem analysis, then describes the business process for submitting village documents, next is process modeling, and finally, conclusion analysis. The study results indicate that the application of the village administration information system described in this research model is proven to facilitate the administrative process and village governance and improve government and community institutions' control and supervision functions. These positive impacts have implications for improving the practice of Good Public Governance, including democracy, transparency, accountability, legal culture, and fairness and equality.